Implementasi Algoritma K-Means Clustering Dalam Menentukan Harga Getah Karet Pada Pabrik Karet Di Bengkulu Tengah - Yulia Darmi; Muntahanah Muntahanah; Ujang Juhardi; Aditya Deko Widodo (UNIVED Press, 2024)
Rubber is a commodity that has been developed by various rubber producing and exporting countries such as Thailand, Malaysia and Indonesia. However, this trade must also go through intense competition between exporting countries. In order to survive in the international market, rubber producing countries must increase their competitiveness by increasing the quality of their rubber processing materials. To improve the quality of rubber, of course, farmers and factories must pay attention to the quality and price of rubber must be in accordance with the quality of the rubber produced. Therefore it is necessary to create a clustering information system to determine the purchase price which will make it easier for the factory to buy rubber latex based on its quality. The information system uses the K-means clustering algorithm to group and determine prices based on the input quality values.